Aging Hallmarks: The Benefits of Physical Exercise - Rebelo-Marques, Alexandre; De Sousa Lages, Adriana; Andrade, Renato; Ribeiro, Carlos Fontes; Mota-Pinto, Anabela; Carrilho, Francisco; Espregueira-Mendes, João (Frontiers in Endocrinology, 2018)
World population has been continuously increasing and progressively aging. Aging is characterized by a complex and intra-individual process associated with nine major cellular and molecular hallmarks, namely, genomic instability, telomere attrition, epigenetic alterations, a loss of proteostasis, deregulated nutrient sensing, mitochondrial dysfunction, cellular senescence, stem cell exhaustion, and altered intercellular communication. This review exposes the positive antiaging impact of physical exercise at the cellular level, highlighting its specific role in attenuating the aging effects of each hallmark. Exercise should be seen as a polypill and improves the health-related quality of life and functional capabilities while mitigating physiological changes and comorbidities associated with aging. To achieve a framework of effective physical exercise interventions on aging, further research on its benefits and the most effective strategies is encouraged.